2006
DOI: 10.1007/s11194-006-9022-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Offenders’ State-of-Mind Regarding Childhood Attachment: A Controlled Investigation

Abstract: Attachment experiences have been regarded as significant by researchers and clinicians attempting to explain the etiology of sexual offending. Although initial studies have revealed some promising evidence, there are a number of theoretical and methodological problems with this preliminary body of work. While addressing these limitations, the goal of the present study was to investigate state-of-mind regarding childhood attachment among subtypes of sexual offenders, comparing them to both a sample of nonsexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Greater proportions of sex offenders report insecure adult attachment styles compared to non-offenders (Baker & Beech, 2004;Jamieson & Marshall, 2000;Marsa et al, 2004;Sawle & Kear-Colwell, 2001;Smallbone & Dadds, 1998) or normative non-offender data (Stirpe, Abracen, Stermac, & Wilson, 2006;Ward, Hudson, & Marshall, 1996). This was only observed for non-familial sex offenders who had abused children in Jamieson and Marshall's (2000) study, with no differences demonstrated between incest offenders and community controls, suggesting a complex relationship might exist in relation to adult attachment and different groups of sex offenders.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Greater proportions of sex offenders report insecure adult attachment styles compared to non-offenders (Baker & Beech, 2004;Jamieson & Marshall, 2000;Marsa et al, 2004;Sawle & Kear-Colwell, 2001;Smallbone & Dadds, 1998) or normative non-offender data (Stirpe, Abracen, Stermac, & Wilson, 2006;Ward, Hudson, & Marshall, 1996). This was only observed for non-familial sex offenders who had abused children in Jamieson and Marshall's (2000) study, with no differences demonstrated between incest offenders and community controls, suggesting a complex relationship might exist in relation to adult attachment and different groups of sex offenders.…”
Section: Introductionmentioning
confidence: 87%
“…This was only observed for non-familial sex offenders who had abused children in Jamieson and Marshall's (2000) study, with no differences demonstrated between incest offenders and community controls, suggesting a complex relationship might exist in relation to adult attachment and different groups of sex offenders. Stirpe et al (2006) found that child molesters were more likely to have preoccupied insecure attachments, while incest offenders and rapists were more likely to have dismissing insecure attachments. Ward et al (1996) found that child molesters were more fearful or preoccupied and less dismissive than rapists, who were similar to violent offenders.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The focus of previous studies among adult male inmates in different countries was mainly comparing sexual offenders with violent offenders revealing that these two groups did not differ significantly in terms of insecure (anxious, avoidant) attachment styles: Abracen et al, (2006;Canadian prisons);Baker, & Beech (2004;English prisons); Hudson & Ward (1997;New Zealand prison);Marsa et al, (2004;Irish prisons); Stripe et al (2006;Canadian prison) ;Ward, Hudson, & Marshall (1996; New Zealand prison). The violent offenders were also noted to be similar to the rapists in that they tended to be more dismissive/avoidant in their attachment styles (Stripe et al, 2006;Ward et al, 1996).…”
mentioning
confidence: 99%